Steel concrete composite systems for modular construction of high-rise buildings. (October 2019) - Liew, J.Y.R.; Chua, Y.S.; Dai, Z.
Abstract: Modular prefabrication technology promotes off-site manufacturing of modules and on-site assembly by improving the construction efficiency, safety and productivity. However, the joining of individual modules needs special connectors that must be fast to install and robust enough to ensure structural integrity. The restrictions on the overall dimension and weight of the modules for lifting and transportation provide the impetus to develop a more efficient structural module system that is lightweight and fast to install. This paper discusses the design and construction challenges of existing modular construction of high-rise buildings and provides solutions to resolve these challenges. A novel lightweight steel-concrete composite system is introduced to reduce the weight of the module without compromising the strength and stiffness. To increase the available headroom, a slim floor system is proposed to reduce the floor-to-floor depth and ensure the integration of buildings service within the structural zone. High strength concrete is used as an infill material for tubular columns to maintain the same column size to avoid complex joining details involving modules with different column sizes. Long-span steel concrete composite modular system is proposed to reduce the number of joints and columns for fast track construction. A fast and easy joining technique is developed to ensure fast installation of modules. Inter-module joints are modelled as semi-rigid to capture the realistic joint behaviour in global analysis to ensure the structural integrity and overall stability of the building. Highlights: Key challenges and solutions for adopting modular construction for high-rise building are discussed. Long span lightweight steel-concrete composite modular system is proposed. Slim floor system is proposed to increase module headroom. Fast and easy joining technique is developed. Stability and robustness analyses of high-rise modular are carried out.